Modified Pro-Self Pain Control to Increase Activity in Patients with Colorectal Cancer - Sujianto, Untung; Mardiyono, Mardiyono; Munawaroh, Khoirunnisa’ (Nurse Media Journal of Nursing, 2017)
Background: Barriers to performing activities of daily living are common complaints of patients with cancer. One of the factors causing these barriers is pain. A modified pro-self pain control is a method used to enhance the patientsâ€™ ability to cope with pain to increase their activity.Purpose: This study aimed to evaluate the modified pro-self pain control to increase activity in patients with colorectal cancer undergoing chemotherapy.Methods: The present study employed an experimental design. Patients with colorectal cancer undergoing chemotherapy were randomly assigned to the intervention group (n=24) and the control group (n=24). The patients in the control group were given a standard hospital intervention, while the patients in the intervention group were given the modified pro-self pain control for nine days. The data were collected using the instrument of KATZ index and analyzed using the independent t-test.Results: The result of this study showed that there was a higher increase of activity among the patients in the intervention group than in the control group. Independent t-test showed that there was a significant difference between the intervention group and the control group (p=0.00).Conclusion: The modified pro-self pain control was found more effective to increase the activity in patients with colorectal cancer undergoing chemotherapy than that of the standard hospital intervention.Â